BALUMBO BIDUK KABUPATEN SAROLANGUN SEBAGAI WARISAN BUDAYA LOKAL DAN MEDIA PENGUATAN PENDIDIKAN KARAKTER - Fitriana, Novita; Mamilah, Dinah; Felicia Azaria Hia, Alice; Setia Fernanda, Luisha; Wulandari, Tri; Zaskia, Rihhadatul; Rohana Rahmayani, Tria; Nur Rahmah ZD, Nadhifa; Ade Novri Yanti Napitu, Vivi; Dalimunthe, Juita; Novi Yanti Br Sirait, Yuken (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the Balumbo Biduk tradition of Sarolangun Regency as a local cultural heritage as well as a medium for strengthening character education in Elementary Schools. The study uses a qualitative approach with descriptive research types and a phenomenological approach to understand the meaning of cultural values ​​​​based on the perspective of tradition practitioners. The research subjects included traditional leaders, organizing committees, elementary school teachers, and fourth-grade students selected through purposive sampling techniques. Data collection techniques were carried out through observation, in-depth interviews, documentation, and literature studies. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions with validity tests through triangulation of sources and techniques. The results of the study show that the Balumbo Biduk tradition not only functions as a community cultural activity, but also contains character values ​​​​relevant to Strengthening Character Education (PPK), namely religious, nationalist, independent, mutual cooperation, and integrity. The value of mutual cooperation is reflected in community cooperation, the value of discipline and integrity is seen in compliance with competition rules, and the value of tolerance and nationalism is seen through community participation across religions and social backgrounds. The integration of the Balumbo Biduk tradition into social studies, civics, Indonesian language, and arts and culture has been proven to increase student participation, cultural awareness, and collaborative attitudes. Thus, Balumbo Biduk can be positioned as an effective contextual learning resource to support local cultural preservation while strengthening character education in elementary schools.